Design of a Continuous Passive Motion (CPM) Machine for Wrist Joint Therapy - Noviyanto, Antonius Hendro; Septilianingtyas, Laurentia Deby; Rahmawati, Dita (Universitas Muhammadiyah Yogyakarta, 2021)
Patients after joint surgery require passive movements that are carried out continuously. The movement is given to the patient to reduce the stiffness that occurs in the joints after joint surgery. Joint stiffness is characterized by pain and limited motion of the joint, which is caused due to reduced synovial fluid. Synovial fluid in the joints can be reduced if the joint is not moved for a long time. This research will design a wrist joint therapy machine that can be moved flexion, extension, ulnar, and radial. Besides that, the device to be designed can be adjusted the angle of movement of the tool and the speed of movement of the tool. The angles of movement that can be reached are (1) flexion movement: 80 ° movement angle, (2) extension movement: 75 ° movement angle, (3) radial movement: 25 ° movement angle, and (4) ulnar movement: movement angle 39 °. Adjustable speeds include 1 RPM, 2 RPM, and 3 RPM. In the result of the testing device, we find the maximum difference of movement in 2° and the speed of rotation we have the difference in 0.5 seconds. Based on experiments that have been done, the tool can be controlled in accordance with the desired movement settings.